2021
DOI: 10.21203/rs.3.rs-956244/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Field Application of Nanoliposomes Delivered Quercetin by Inhibiting Specific hsp70 Gene Expression Against Plant Virus Disease

Abstract: The annual economic loss caused by plant viruses exceeds 10 billion dollars due to the lack of ideal control measures. Quercetin is a flavonol compound that exerts a control effect on plant virus diseases, but its poor solubility and stability limit the control efficiency. Fortunately, the development of nanopesticides has led to new ideas. In this study, 117 nm quercetin nanoliposomes with excellent stability were prepared from biomaterials, and few surfactants and stabilizers were added to optimize the formu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…In vitro Quercetin, quercetin-3′-sulfate, and Quercetin has a preventive efect on plant virus infections. Wang et al [80] optimized the prescription by adding a few of surfactants and stabilizers using biomaterials as raw materials to obtain 117 nm quercetin nanoliposomes with good stability. Tey found that Nbhsp70er-1 and Nbhsp70c-A were target genes for quercetin and that nanoliposomes had a 33.6% and 42% increase in inhibition at gene and protein levels, respectively.…”
Section: Human Breast Cancermentioning
confidence: 99%
“…In vitro Quercetin, quercetin-3′-sulfate, and Quercetin has a preventive efect on plant virus infections. Wang et al [80] optimized the prescription by adding a few of surfactants and stabilizers using biomaterials as raw materials to obtain 117 nm quercetin nanoliposomes with good stability. Tey found that Nbhsp70er-1 and Nbhsp70c-A were target genes for quercetin and that nanoliposomes had a 33.6% and 42% increase in inhibition at gene and protein levels, respectively.…”
Section: Human Breast Cancermentioning
confidence: 99%
“…20,21 Studies have shown that quercetin nanoliposomes can inhibit TMV by specifically inhibiting the expression of Hsp70 in N. benthamiana. 22 In addition, a polysaccharide was found in Dendrobium nobile, which can stimulate calcium signaling pathway and promote host defense against TMV infection. 23 In our previous study, 37 new pyrimidine moroxydine derivatives were synthesized by fusing pyrimidine heterocycles and moroxydine skeleton, and their antiviral activities against TMV were tested.…”
Section: Introductionmentioning
confidence: 99%
“…Polysaccharide peptides, lentinan and ursolic acid can promote the expression of defense‐related enzymes, such as phenylalanine ammonia‐lyase (PAL) and peroxidase (POD), as well as defense‐related genes in host plants, thus increasing the resistance and tolerance of plants to TMV 20,21 . Studies have shown that quercetin nanoliposomes can inhibit TMV by specifically inhibiting the expression of Hsp70 in N. benthamiana 22 . In addition, a polysaccharide was found in Dendrobium nobile , which can stimulate calcium signaling pathway and promote host defense against TMV infection 23 …”
Section: Introductionmentioning
confidence: 99%